Pharmacological treatment with annexin A1-derived peptide protects against cisplatin-induced hearing loss - Sena, Letícia S.; Sasso, Gisela R.S.; Sanches, José Marcos; Franco, Paulo C.; Azevedo, Marisa F.; Oliani, Sonia M. [UNESP]; Gil, Cristiane D. [UNESP] (Elsevier, 2022)
Cisplatin is an antineoplastic agent widely used, and no effective treatments capable of preventing cisplatin-induced ototoxicity and neurotoxicity in humans have yet been identified. This study evaluated the effect of the anti-inflammatory annexin A1 (AnxA1)-derived peptide Ac2–26 in a cisplatin-induced ototoxicity model. Wistar rats received intraperitoneal injections of cisplatin (10 mg/kg/day) for 3 days to induce hearing loss, and Ac2–26 (1 mg/kg) was administered 15 min before cisplatin administration. Control animals received an equal volume of saline. Hearing thresholds were measured by distortion product otoacoustic emissions (DPOAE) before and after treatments. Pharmacological treatment with Ac2–26 protected against cisplatin-induced hearing loss, as evidenced by DPOAE results showing similar signal–noise ratios between the control and Ac2–26-treated groups. These otoprotective effects of Ac2–26 were associated with an increased number of ganglion neurons compared with the untreated cisplatin group. Additionally, Ac2–26 treatment produced reduced immunoreactivity on cleaved caspase 3 and phosphorylated ERK levels in the ganglion neurons, compared to the untreated group, supporting the neuroprotective effects of the Ac2–26. Our results suggest that Ac2–26 has a substantial otoprotective effect in this cisplatin-induced ototoxicity model mediated by neuroprotection and the regulation of the ERK pathway.
Keywords: Ac2–26; Cisplatin; Distortion product otoacoustic emissions; Inner ear; Neuron; Rat; Scanning electron microscopy